Further Silencing the Voiceless: The Role of Gatekeepers in Accessing Information about Self-Injury - Hasking, Penelope; Lewis, S.P.; Staniland, Lexy; Mirichlis, Sylvanna; Hird, Kirsty; Gray, Nicole; Arai, Mia; Pemberton, Ethan; Preece, David; Boyes, Mark (LIPPINCOTT WILLIAMS & WILKINS, 2023)
Gatekeepers play a pivotal role in protecting individuals under their care and are central to keeping people safe and away from harm. In the field of nonsuicidal self-injury (NSSI), a range of gatekeepers exist, including those who protect access to vulnerable research participants, those who protect school children, those charged with making decisions about funding priorities, and those in charge of clinical care for people who self-injure. The aim of this commentary is to outline the roles these different gatekeepers have in protecting access to research participants, access to NSSI knowledge, and access to clinical care for individuals who self-injure. We provide examples in which gatekeepers may present barriers and offer solutions for how to work with gatekeepers for mutual benefit.